2007
DOI: 10.1111/j.1469-8749.2007.00312.x
|View full text |Cite
|
Sign up to set email alerts
|

Handwriting development, competency, and intervention

Abstract: Failure to attain handwriting competency during the schoolage years often has far-reaching negative effects on both academic success and self-esteem. This complex occupational task has many underlying component skills that may interfere with handwriting performance. Fine motor control, bilateral and visual-motor integration, motor planning, inhand manipulation, proprioception, visual perception, sustained attention, and sensory awareness of the fingers are some of the component skills identified. Poor handwrit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

15
510
1
49

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 616 publications
(575 citation statements)
references
References 57 publications
15
510
1
49
Order By: Relevance
“…The component skills that enable the motor activity of picking up a pen or pencil and drawing an alphanumerical symbol are both complex and diverse [2]. Nonetheless, the fundamental challenge is one of learning how to generate motor commands that result in an effector (the hand) producing a graphical representation of a memorized shape (alphanumerical symbol).…”
Section: Introductionmentioning
confidence: 99%
“…The component skills that enable the motor activity of picking up a pen or pencil and drawing an alphanumerical symbol are both complex and diverse [2]. Nonetheless, the fundamental challenge is one of learning how to generate motor commands that result in an effector (the hand) producing a graphical representation of a memorized shape (alphanumerical symbol).…”
Section: Introductionmentioning
confidence: 99%
“…Ainda segundo as autoras, o prejuízo nessas habilidades pode resultar em caligrafia ilegível e comprometer o desempenho acadêmico da criança 13 .…”
Section: Discussionunclassified
“…Several handwriting performance skills have been identified that should be mastered before a child can be successful at handwriting. Prerequisites for handwriting include the ability to cross midline, recognize letters of the alphabet, demonstrate established hand dominance, use functional pencil grasp, copy geometric shapes, use hand-eye coordination, and demonstrate proper sitting posture (Feder & Majnemer, 2007;Marr, Windsor, & Cermak, 2001;Rosenblum et al, 2003 Research indicates that fine motor skill deficits contribute to handwriting challenges (Cornhill & Case-Smith, 1996;Smits-Engelsman, Niemeijer, & van Galen, 2001). In addition, children who had difficulty with handwriting skills and had slow performance were found to have visual-motor integration challenges (Tseng & Chow, 2000;Volman, van Schendel, & Jongmans, 2006 Miller, 2006).…”
Section: Components Of Handwritingmentioning
confidence: 99%
“…Successful handwriting requires a seamless integration of cognition, fine motor control, in-hand manipulation, visual-motor integration, motor planning, visual perception, and sustained attention (Feder & Majnemer, 2007;Rosenblum, Weiss, & Parush, 2003). Handwriting skills begin developing during the pre-school years with universal characteristics that all written languages share.…”
Section: Introductionmentioning
confidence: 99%